Inversão do ônus da prova no código de defesa do consumidor - Cunha, Alexandre Luna da (2007)
The Brazilian Consumer Protection and Defense Code rules the principles for shift of evidence burden. This paper broaches the relation between citizenship, legal process and consumer rights besides bringing to a focus the shift of evidence burden. It goals to develop the idea that the application of shift of evidence burden must consider the principles of easing access to the justice for the consumer, and putting into effect his rights. It also explores the functioning of shift of evidence burden in consumer area.